A putative transcription factor MYT2 regulates perithecium size in the ascomycete Gibberella zeae. - Yang Lin; Hokyoung Son; Kyunghun Min; Jungkwan Lee; Gyung Ja Choi; Jin-Cheol Kim; Yin-Won Lee (PLoS ONE, 2012)
The homothallic ascomycete fungus Gibberella zeae is a plant pathogen that is found worldwide, causing Fusarium head blight (FHB) in cereal crops and ear rot of maize. Ascospores formed in fruiting bodies (i.e., perithecia) are hypothesized to be the primary inocula for FHB disease. Perithecium development is a complex cellular differentiation process controlled by many developmentally regulated genes. In this study, we selected a previously reported putative transcription factor containing the Myb DNA-binding domain MYT2 for an in-depth study on sexual development. The deletion of MYT2 resulted in a larger perithecium, while its overexpression resulted in a smaller perithecium when compared to the wild-type strain. These data suggest that MYT2 regulates perithecium size differentiation. MYT2 overexpression affected pleiotropic phenotypes including vegetative growth, conidia production, virulence, and mycotoxin production. Nuclear localization of the MYT2 protein supports its role as a transcriptional regulator. Transcriptional analyses of trichothecene synthetic genes suggest that MYT2 additionally functions as a suppressor for trichothecene production. This is the first study characterizing a transcription factor required for perithecium size differentiation in G. zeae, and it provides a novel angle for understanding sexual development in filamentous fungi.